The Relationship Between Protein Intake, Iron (Fe) Intake, and Diet Quality with Hemoglobin Levels Among Female Undergraduate Nutrition Students at Universitas Negeri Surabaya (A Secondary Data Analysis) - Nur Choiriyah, Diva; Sholihah, Lini Anisfatus (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Anemia is a condition in which the body lacks healthy red blood cells or when red blood cells do not function properly. A person is considered anemic when their hemoglobin level <12 g/dL. Theoretically, hemoglobin levels can be influenced by dietary patterns. This study aims to analyze the relationship between protein intake, iron (Fe) intake, and diet quality based on the Diet Quality Index-International (DQI-I) score and hemoglobin levels among undergraduate students of the Nutrition Science Program at the State University of Surabaya. This research is a quantitative study using an observational analytic approach with a cross-sectional design. The sample was selected through cluster random sampling, resulting in a total of 106 respondents. The instrument used to assess dietary intake was a 3-day non-consecutive food record, and the respondent’s hemoglobin levels were measured using a hemoglobin meter (Easy Touch). The collected data were analyzed using the Pearson correlation test. Based on the results of the Pearson correlation analysis, the significance values and correlation coefficients were as follows: protein (p = 0.465; r = 0.072), iron (p = 0.671; r = 0.042), and diet quality (p = 0.311; r = 0.099) in relation to hemoglobin levels among students of the Nutrition Science Program at State University of Surabaya. These results indicate that there is no significant relationship between protein intake, iron intake, or diet quality and hemoglobin levels in this population. It is recommended that future research consider other potential factors contributing to anemia, such as infections, the habitual consumption of tea, coffee, or other nutrient absorption inhibitors, as well as physical activity and menstrual status.